KORELASI KECERDASAN EMOSIONAL (EQ) DENGAN JIWA LEADERSHIP PESERTA DIDIK - Afifah, Afifah; Mashuri, Imam (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2025)
Effective leadership has elements of emotional intelligence, namely self-awareness, self-management and social awareness. With this awareness, a leader's emotions are useful in directing the power of emotions to improve self-satisfaction, morale and motivation to get better results. Therefore, the background of this research is that emotional intelligence (EQ) influences students' leadership spirit. The purpose of this research is to determine emotional intelligence (EQ), to determine the leadership spirit of students and to determine the correlation between emotional intelligence (EQ) and the leadership spirit of students. This type of research is quantitative research using observation, questionnaire and documentation techniques. Meanwhile, to analyze the data using parametric inferential statistical analysis and percentage formulas. The results of this research show that students' emotional intelligence (EQ) is in the